General geology and seismic refraction investigation of UMK Jeli Campus, Jeli, Kelantan - Ahmad Fadhli Kamarollzaman (2013)
The study area is located in the vicinity of University Malaysia Kelantan Jeli Campus, Jeli, Kelantan covering a total area of 5 square kilometers within the range of the coordinates latitude 5 ° 4315 " to 5 ° 45'30 " N and longitude 101 ° 51'15 101 ° 53'30 " to " E. The study is divided into two parts, the geological mapping covering the broad area of 5 kilometers square and seismic refraction investigations which focused on the development site within the campus. The purpose of the research is to study the general geology, determine the subsurface conditions and provide support data for engineering purposes. The geological mapping conducted indicates that the area is dominated by granite estimated to be Triassic age based on previous research. Analysis of macroscopic and microscopic based on observations and thin section classifying the granitic rocks into medium to coarse grained biotite granite and microgranite. Colluvium deposits which cover the hillside and foothill are also recorded. However, only the granite rocks that able to be mapped due to it's widely distribution compared colluvium which limited distributed and not mappable. Seismic investigations identified that the development site of campus consists of four layers; the layer of soil, the layer of unconsolidated clay, silt or unconsolidated sand, gravel, the layer of weathered or sheared granite bedrock and the layer of fresh granite bedrock layer. The depth of the bedrock at the site varies with the deepest recorded around 20 meters and the shallowest about 5 meters.